A unique familial leukodystrophy with adult onset dementia and abnormal glycolipid storage: a new lysosomal disease?. Issue 2 (1st August 1998) - Simon, David K; Rodriguez, Michael L; Frosch, Matthew P; Quackenbush, Elizabeth J; Feske, Steven K; Natowicz, Marvin R
Abstract : Two adult siblings with early onset dementia are described. At presentation, in their early 30s, they showed poor judgment and disinhibition. A progressive dementia ensued over several years. Brain MRI disclosed diffusely increased T2 signal in the cerebral white matter, suggestive of a leukodystrophy. Numerous lysosomal enzyme assays including leucocyte arylsulphatase A and galactocerebrosidase activities, plasma and fibroblast very long chain fatty acid concentrations, and urinary sulphatide concentrations were normal, as were CSF analyses. A brain biopsy disclosed periodic acid Schiff (PAS) and Sudan black positive material in perivascular macrophages which, by electron microscopy, consisted of stacks of straight or curvilinear paired membranes within angulate lysosomes, indicative of abnormal glycolipid accumulation. The combination of clinical, radiological, biochemical, and pathological features of this degenerative disease is not consistent with that of any of the known leukodystrophies or lysosomal storage disorders. These findings suggest a previously undescribed familial glycolipid storage disorder causing an adult onset leukodystrophy and presenting with behavioural symptoms that mimic a psychiatric disorder.